Electrodeposited Ni–Mo coatings as electrocatalytic materials for green hydrogen production. Issue 4 (April 2023) - Protsenko, V.S.; Bobrova, L.S.; Butyrina, T.E.; Baskevich, A.S.; Korniy, S.A.; Danilov, F.I.
Abstract: In this work, nanocrystalline nickel and nickel-molybdenum alloys were electrodeposited from electrolytes based on deep eutectic solvents. Eutectic mixtures of choline chloride with ethylene glycol (ethaline) and urea (reline) were used as typical representatives of deep eutectic solvents. The deposited Ni and Ni–Mo films were evaluated as potential electrocatalytic materials for green hydrogen production via electrolysis of alkaline aqueous solutions. The electrodeposited samples were characterized by XRD, SEM and EDX techniques, and the electrochemical behavior was evaluated by means of linear voltammetry and Tafel analysis. It was shown that the deposition of nickel (without molybdenum) from the electrolytes based on ethaline provides a higher electrocatalytic activity of the material with respect to the hydrogen evolution reaction than the material deposited from the reline-based electrolytes. The reline-based plating electrolytes contribute to a greater inclusion of molybdenum in the fabricated Ni–Mo alloys and therefore ensure increased electrocatalytic activity as compared with the ethaline-based electrolytes. The electrocatalytic behavior well correlates with the molybdenum content in the coatings. Ni and Ni–Mo electrodeposits produced from the deep eutectic solvent-mediated plating baths exhibit improved electrocatalytic performance and can be considered as promising catalytic materials for water electrolysis in green hydrogen energy. Graphical abstract: Image 1